2006
DOI: 10.1590/s0103-50532006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Two different modes for copper(II) ion coordination to quinine-type ligands

Abstract: Três novos complexos de cobre(II) com os ligantes quinuclidina [Cu(C 7 O (3) have been isolated and characterized. The binding sites were assigned on the basis of vibrational spectroscopy, electron paramagnetic resonance, and thermal analysis results. The possibility of the involvement of the quinuclidinic nitrogen in the coordination was evidenced in complex 1, in which copper(II) is coordinated to two quinuclidine molecules. In the case of quinine-type ligands, if the starting material is deprotonated in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…The onset of the quinine degradation takes places from 243 °C (exothermic peak) as it can be seen in Fig. lb, due to the decomposition of the quinoline moiety (heterocyclic aromatic compound belonging to quinine molecule), which is accompanied by a weight loss of 14 wt%, in concordance with literature [27,28]. The greatest weight loss (above 70%) occurs from 373 °C, reaching the end of the decomposition at 497 °C.…”
Section: Experimental 3 Results and Discussionsupporting
confidence: 85%
“…The onset of the quinine degradation takes places from 243 °C (exothermic peak) as it can be seen in Fig. lb, due to the decomposition of the quinoline moiety (heterocyclic aromatic compound belonging to quinine molecule), which is accompanied by a weight loss of 14 wt%, in concordance with literature [27,28]. The greatest weight loss (above 70%) occurs from 373 °C, reaching the end of the decomposition at 497 °C.…”
Section: Experimental 3 Results and Discussionsupporting
confidence: 85%
“…5). The loading of QUI on the CS–MMT nanocomposites was confirmed, as higher weight loss for CS–MMT/QUI compared with CS–MMT in the 200–500 °C region was observed due to decomposition of QUI 75. A decrease in the weight loss in temperature region around 600–700 °C was observed due to interaction of surface OH groups with adsorbed QUI 24, 73.…”
Section: Resultsmentioning
confidence: 75%
“…Desorption data (Table 2) showed that no appreciable change occurred after the second hour during which the elution of quinine attained equilibrium in the system. On the basis of these results and what is known about the constituents of G. kola [8,17,18], it appears that the adsorption of quinine on G. kola may have occurred by physical adsorption and perhaps by some degree of chemisorption.…”
Section: Discussionmentioning
confidence: 83%
“…Secondly, G. kola also contains trace elements or minerals such as calcium, aluminum, magnesium, potassium, sodium, zinc and copper [16], some of which are known to cause drug interactions through chelate formation [8,17]. It is known that quinine may also act as a ligand by forming a stable five-membered ring with some metals through the quinuclidinic nitrogen and the hydroxyl oxygen, or by binding through the quinolinic aromatic nitrogen [18].…”
Section: Discussionmentioning
confidence: 99%